The big book of Bible questions - Wright, Sally Ann; Grudina, Paola Bertolini (Quezon City : Lampara Publishing, 2023)
"These simple questions, drawn from the lives of all the main characters in the Bible and covering all the main events, will delight, challenge and amuse."--Cover.
Originally published by Anno Domini Publishing, England.
Keywords: Bible -- Study and teaching -- Juvenile literature